Outcomes of transsphenoidal surgery for pituitary adenomas in Spain: a retrospective multicenter study - Paja, Miguel; Soto, Alfonso; Hanzu, Felicia A.; Guerrero-Pérez, Fernando; Cámara, Rosa; Moure, Dolores; Gálvez, Ángeles; Simó-Servat, Andreu; Villar-Taibo, Rocío; Calatayud, María; Vicente, Almudena; Recio-Córdova, Jose M.; et al. (Frontiers in Endocrinology, 2025)
BackgroundThe outcomes of transsphenoidal surgery (TSS) for pituitary adenoma (PA) depend on many factors, including the availability of an expert team and the volume of surgeries performed. Data on the outcomes of TSS for PA are scarce in our country. TESSPAIN evaluates TSS outcomes in Spanish centers to assess the influence of surgical volume and specialized neurosurgical teams on success and complication rates.MethodsA retrospective, nationwide, study of Spanish centers performing TSS between January 2018 and December 2022. Centers were classified as high volume (HV) [n=11, defined as centers with recognized expertise in Spain or those performing more than 25 TSS/year] or non-HV. Data collection included surgical success rates, complications, and pituitary adenoma resectability (R-PA). Additional analyses evaluated the impact of dedicated neurosurgical teams (DNT) within HV centers.ResultsA total of 2815 TSS from 29 Spanish centers were included (1421 NSPA, 436 GH-secreting, 323 Cushing’s disease, 127 PRL-secreting and 25 TSH-secreting PA). The overall success rate was 50.5%, 76.8% for R-PA. HV centers had a higher overall success rate (53.1 vs. 47.7%; p=0.03). Better TSS outcomes for NSPA accounted for this difference. The overall TSS complication rate was 22.1%, which was higher for NSPA than for SPA (25.0 vs. 17.7%). The overall complication rate of TSS for PA was significantly higher in non-HV centers than in HV centers (24 vs 20.4.0; p <0.01). Centers with a DNT showed a trend to higher success rate in R-PA, while having a lower overall incidence of complications in TSS for PA than HV centers without a DNT (18.5 vs. 23.0; p=0.058), mainly reducing the rate of permanent ADH deficiency in all TSS for PA (2.7 vs. 8.4%; p<0.001).ConclusionHigher surgical volume and DNT are associated with improved TSS outcomes for PA in Spain. Our results support the recommendation of concentration of pituitary surgery in a reduced number of centers of expertise in our country in order to improve the success rate and reduce complications, mainly postoperative ADH deficiency.